Long-term effects of cladribine tablets on MRI activity outcomes in patients with relapsing–remitting multiple sclerosis: the CLARITY Extension study - Comi, Giancarlo; Cook, Stuart; Rammohan, Kottil; Soelberg Sorensen, Per; Vermersch, Patrick; Adeniji, Abidemi K.; Dangond, Fernando; Giovannoni, Gavin (Therapeutic advances in neurological disorders, 2018)
Background The CLARITY and CLARITY Extension studies demonstrated that treatment of relapsing–remitting multiple sclerosis (RRMS) with cladribine tablets (CT) results in significant clinical improvements, compared with placebo. This paper presents the key magnetic resonance imaging (MRI) findings from the CLARITY Extension study. Methods Patients who received a cumulative dose of either CT 3.5 or 5.25 mg/kg in CLARITY were rerandomized to either placebo or CT 3.5 mg/kg in CLARITY Extension. Patients from the arm that received placebo in CLARITY were assigned to CT 3.5 mg/kg. MRI assessments were carried out when patients entered CLARITY Extension and after Weeks 24, 48, 72 and 96, and in a supplemental follow-up period. Results At CLARITY Extension baseline, patients who received placebo during CLARITY had more T1 gadolinium-enhanced (Gd+) lesions than patients who received CT during CLARITY. These patients, who were then exposed to cladribine 3.5 mg/kg during the extension, experienced a 90.4% relative reduction (median difference −0.33, 97.5% confidence interval −0.33–0.00; p < 0.001) in T1 Gd+ lesions at the end of the extension compared with the end of CLARITY. Overall, the majority of patients in each treatment group remained free from T1 Gd+ lesions throughout CLARITY Extension. However, a small proportion of patients who were treated with cladribine in CLARITY and received placebo in CLARITY Extension showed evidence of increased MRI activity, and this was associated with a prolonged treatment gap between CLARITY and CLARITY Extension. Conclusion A 2-year treatment with CT 3.5 mg/kg has a durable effect on MRI outcomes in the majority of patients, an effect that was sustained in patients who were not retreated in the subsequent 2 years after initial treatment. ClinicalTrials.gov identifier: NCT00641537